The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.bpj.2018.01.038
|View full text |Cite
|
Sign up to set email alerts
|

The Antiparallel Dimerization of Myosin X Imparts Bundle Selectivity for Processive Motility

Abstract: Myosin X is an unconventional actin-based molecular motor involved in filopodial formation, microtubule-actin filament interaction, and cell migration. Myosin X is an important component of filopodia regulation, localizing to tips of growing filopodia by an unclear targeting mechanism. The native α-helical dimerization domain of myosin X is thought to associate with antiparallel polarity of the two amino acid chains, making myosin X the only myosin that is currently considered to form antiparallel dimers. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Myosin X and VI have also been shown to exhibit gating of ADP release from AM,ADP (31)(32)(33). Myosin VI binds ATP relatively slowly and this step also is probably gated by mechanical strain between its heads.…”
Section: Implications Of Negatively Strained Actomyosin Attachmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myosin X and VI have also been shown to exhibit gating of ADP release from AM,ADP (31)(32)(33). Myosin VI binds ATP relatively slowly and this step also is probably gated by mechanical strain between its heads.…”
Section: Implications Of Negatively Strained Actomyosin Attachmentsmentioning
confidence: 99%
“…1 B, states d / e; (22)(23)(24)(25)(26)(27)). This is also observed when the strain becomes negative for nonmuscle myosins (28)(29)(30)(31)(32)(33). This ''gating'' of the actomyosin mechanochemical cycle, which enables load-dependent energy transduction in muscle and synchronizes the biochemical reactions in processive myosins, is thought to arise from stress-and straindependent kinetics of the underlying chemical and structural transitions.…”
mentioning
confidence: 98%
“…The expressions may be derived using matrix algebra, and can also be straightforwardly implemented for fitting experimental data. Our approach shares some similarities with the strategies adopted in (27) and (47) to extract the velocity and processivity for kinetic models of myosin VI, and X, respectively. However, our results have the benefit of an analytical solution which holds regardless of the underlying structure of the kinetic network.…”
Section: Significance Statementmentioning
confidence: 99%
“…This demonstrated that oligomerization is strictly required for targeting of Myo10 in our cell system. We utilized a similar design as previously described to create a parallel dimerized Myo10 (Caporizzo et al, 2018), in which a GCN4 sequence was fused in register with its SAH motif (Figure 6A; Myo10-MN-GCN4). This form of Myo10 was shown to be active in vitro, exhibiting processive motility on both single actin filaments and fascin-bundled actin (Caporizzo et al, 2018).…”
Section: Mode Of Oligomerization and Motor Domain Identity Influence Actin Track Selectionmentioning
confidence: 99%